Perdida na Sociedade das Maravilhas - Leite, Kivya Marin de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O projeto é a construção da pré-produção de um curta metragem animado mudo e se trata de uma obra autoral que aborda a ansiedade do mundo moderno e suas consequências, trazendo elementos que possam transmitir ao espectador sensações para ter uma compreensão além de palavras. As etapas dessa pré-produção incluem o briefing, criação de roteiro, storyboard e concept art dos personagens.

The project consists of building the pre-production pf a silent animated short film, which is an original work addressing the anxiety of the modern world and its consequences, incorporating elements that aim to evoke sensations in the viewer for a deeper understanding beyond words. The stages of this pre-production of silent animated short film, which is an original work addressing the anxiety of the modern world and its consequences, incorporating elements that aim to evoke sensations in the viewer for a deeper understanding beyond words. The stages of this pre-production includ briefing script writing story board, and character concept art.
Lost in the Wonderland Society
Keywords: Design gráfico; Animação (cinematografia); Arte conceitual; Ilustração; Cartoon characters; Animation; Concept art; Ilustration; Pre-production